Congenital Tubal Anomalies: Exploring Their Relationship with Tubal Factor Infertility an Observational-Descriptive Study - Güler İsrafilova; Emre Pabuccu; Denizhan Deniz; Recai Pabuccu (Clinical and Experimental Obstetrics & Gynecology)
Background: Infertility represents a significant global concern affecting millions of couples worldwide. Among the various causes contributing to infertility, tubal factor infertility (TFI) emerges as a prominent factor that warrants closer investigation. Such abnormalities may originate from multiple causes, including congenital tubal anomalies (CTAs). This study aimed to reveal the prevalence of CTAs and associated pathologies among patients diagnosed with TFI. Methods: This observational study was conducted at two centers (University Hospital and a referral infertility clinic), between 2020 and 2023. Diagnostic laparoscopy was offered to all women diagnosed with TFI after hysterosalpingography (HSG) and who did not achieve pregnancy within six months after the examination. Patients who consented to undergo diagnostic laparoscopic were included in the study. Results: After the initial infertility work-up, 895 women (21%) were diagnosed with suspected TFI. Out of these, 220 women consented to undergo diagnostic laparoscopy. Among them, 113 (51.3%) were found to have surgically confirmed tubal pathologies/anomalies, while 107 (49.7%) revealed normal findings. A total of 34 women (15%) were found to have, total or partial agenesis, among which 32 revealed congenital uterine anomalies, and 16 revealed other system anomalies. Conclusions: CTAs contribute significantly more to TFI than expected in the general population. Therefore, careful systemic examinations, especially for uterine anomalies, are essential.